Syncretism and the Politics of the Tingkeban in West Java - Newland, Lynda (The Australian journal of anthropology, 2001)
For the rural Sundanese of West Java who identify with Nahdatul Ulama Islam, the tingkeban is considered a mandatory ritual to be conducted for a woman who is seven months pregnant. However, like other local practices around birth, the tingkeban has come under state and urban modernising influences that have attempted to displace some of its elements as ‘culture’ rather than ‘religion’ and to discredit many of these as superstitious and backward. This paper examines the ritual elements of the tingkeban that produce and reinforce local cosmological and ontological ideas about the nature of personhood and society, and, in particular, how the ritual highlights the ambivalent status of the villagers within broader relations of power such as the Indonesian State and other forms of Islam existing in Indonesia. The paper also explores how the assumptions within the ideology of modernisation propagated under the last years of the Suharto regime coincide with assumptions in scholarly work such as those underlying Geertz's depiction of the syncretic nature of Javanese religion.